The body of Brooklyn - Lazar, David, 1957- (Sightline books., 2003)
In The Body of Brooklyn David Lazar, an acclaimed essayist and prose stylist, offers a vividly detailed, hilarious, and touching recollection of his Brooklyn upbringing in the 1960s and 70s. His immigrant Jewish heritage and his bodily history--from the travails of childhood obesity to the sexual triumphs of post-adolescent leanness--form the core of this series of essays, all of which will win the interest and admiration of readers.